Foreign Experience in The Selection, Training and Development of Bank Employees (European Journal of Economics, Finance and Business Development, 2023)
In today's increasingly competitive business world, the right selection, recruitment and training of employees is one of the main factors of success. The banking industry is no exception, and many companies in this industry strive to attract the best employees and create an effective team. One of the ways to achieve this goal is to study foreign experience in the selection, recruitment and training of employees. Leading companies in the USA, Europe and Asia have long understood the importance of proper HR management and have invested heavily in this area.